Characterization of Unusual Human Group A Rotavirus VP4 Geno- type Detected in Moroccan Children Fully Vaccinated with Rotarix. Issue 2 (April 2020) - Boulahyaoui1, Hassan; Amine1, Sanaa Alaoui; Melloul, Marouane; Hilali5, Farida; El-Fahime1, Elmostafa; Toui, Saad Mrani1 and Nadia
No abstract available